Can hydrogen and Carbon Capture and Storage (CCS) help decarbonize the coal power plants in Asia? - Ali Habib (The Oxford Institute for Energy Studies, 2024)
As the power sector is the largest GHG emitter, it is important to investigate the fuels used in this sector. In 2023, coal was the primary source of electricity supply, accounting for 35.9%. Natural gas came in second, representing 23%. Asia has the largest number of coal plants in operation, standing at a capacity of 1,667 GW, which is more than seven times the next region, North and Latin America. Eastern Asia is the largest subregion, with an installed coal plant capacity of 1,261 GW, representing 76% of the total capacity. China leads the pack with the highest installed capacity, accounting for a staggering 68.17% of the total capacity. India comes in second place, with a respectable 14.22% installed capacity. The coal plants mentioned above emit an estimated 7,610 million tons of CO2 annually. China and India are the top emitters, responsible for 67.45% and 14.57% of the total emissions, respectively. Between 2000 and 2023, 151 GW of coal plants were retired in Asia and around 1,553 GW of plants were cancelled from 2010 to 2023. Nonetheless, 80 GW of coal plant plans have been announced, 105 GW in the pre-permit phase, 171 GW have been permitted, and 193 GW are currently under construction. This paper aims to investigate the potential of hydrogen technology and synergies with the Carbon Capture and Storage (CCS) technology in mitigating carbon emissions from coal power plants in Asia. The paper first looks at the environmental footprint of coal fired power plants, then considers ammonia substitution as a means of reducing that impact, and finally discusses the potential of CCS as a pathway to decarbonization, including an introduction to the pairing of the nascent Oxy-fuel combustion technology with CCS, potentially combined with green hydrogen production, as a decarbonization pathway.
Keywords: 330; Asia; CCS; Co-firing; Coal; decarbonization; green ammonia; Hydrogen; Japan; Oxy-Fuel; Power Sector